In memoriam Björn Sigurðsson born 100 years ago - Sigurður Ingvarsson 1956- (2013)
Björn Sigurðsson was appointed the first director and founder of the Institute for Experimental Pathology, University of Iceland at Keldur, in 1946. Research started in new facilities in 1948, focused from the beginning on diseases in sheep. This was specifically due to new infections imported into Iceland in 1933 by Karakul sheep, wich were causing paratuberculosis, maedi/visna and adenomatosis/jaagsiekte diseases.